Critical Analysis of Guidelines for Providing Sedation to Patients Undergoing Gastrointestinal Endoscopy Procedures - Goudra, Basavana (Anesth Essays Res, 2019)
In spite of growing numbers of gastrointestinal endoscopic procedures performed under deep sedation, guidelines are lacking. Hypoxemia and aspiration continue to be the main source of morbidity. Anesthesia providers have tried to address these concerns by modifying their technique and employing newer or improvised devices. In addition, preprocedural evaluation poses many challenges. In many centers, workload pressures determine the time available to perform such an evaluation. A comprehensive history and examination similar to a major surgical procedure is often not possible. As a result, a focused history and examination is essential. This should be followed by an appropriate explanation of risks before obtaining consent. A plan should be in place to manage complications such as aspiration. This paper provides a succinct review of the above aspects.